Nilai-Nilai Dan Hukum Duan Lolat - Yeheskel Wessy; Lodwyk Wessy (Program Studi Hukum Diluar Kampus Utama Universitas Pattimura Kabupaten Maluku Barat Daya, 2024)
In accordance with the nature of nature, humans from birth until death live together with other humans. Or in other words, humans cannot live alone, separated from other human groups. Since time immemorial, humans have had a desire to gather with each other in a group, besides that, humans have had a desire to be in society. Aristotle stated that humans are zoon politicization, which means that humans as creatures basically always want to socialize and gather with fellow humans because humans are social creatures. Customary law contains a traditional nature, stems from the will of ancestors who are usually deified and custom is also considered to be based on the will of the gods. Customary law comes from customs. Customs are a collection of social rules that have existed for a long time, have become a tradition in society, and which are intended to regulate the order of that society. These rules are obeyed in a legal association. Not all customary rules are positive law. Because besides sanctioned customs, there are also non-sanctioned customs. The emergence of the Duan Lolat culture as the highest customary law (adatrecht) began with a form of marriage, which used to be understood that an ideal marriage was one that occurred within one's own circle, and it was forbidden to carry out marriages outside one's group. The social grouping system in what is called Duan Lolat does not construct standard social strata/classes like the caste system. Duan as the giver of the daughter, Lolat as the recipient of the daughter in a Tanimbar marriage, from which the marriage gives rise to their respective rights and obligations which should and should not be implemented from the time the marriage occurs up to a certain level of descent.